(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
Uzbekistan pursues a nationally defined economic development path, with economic growth driven by the effective implementation of investment policy. A well-implemented investment policy and a favourable investment climate are essential for sustained GDP growth in the country.